Binder’s syndrome - Jain, Upendra (BMJ Publishing Group, 2011)
Binder syndrome or maxillonasal dysplasia is an uncommon developmental anomaly affecting primarily the anterior part of the maxilla and nasal complex. The characteristic findings are a failure of development in the premaxillary area with associated deformities of the nasal skeleton and the overlying soft tissues. Affected individuals typically have an unusually flat, underdeveloped midface (midfacial hypoplasia), with an abnormally short nose and flat nasal bridge, underdeveloped upper jaw, relatively protruding lower jaw and/or a ‘reverse overbite’ (or class III malocclusion). A 16-year-old female reported to clinic with chief complaint of facial deformity, on examination patient had classical feature of maxillonasal dysplasia. A brief review of the condition and the proposed multi-disciplinary treatment plan is discussed.